Endoplasmic reticulum-targeting activatable nanophotosensitizers for hypoxia relief and enhanced photodynamic therapy - Diao, Shanchao; He, Xiaowen; Wu, Ying; Yin, Likun; Huang, Yuxin; Zhou, Wen; Xie, Chen; Fan, Quli (Chemical science (Cambridge), 2025)
Photodynamic therapy (PDT) is a promising cancer therapeutic modality. However, the specific targeting capability of conventional photosensitizers is relatively low, which significantly suppresses the efficacy of PDT. In this study, an endoplasmic reticulum (ER)-targeting nanophotosensitizer (TPPa-Y NP) was designed and prepared for enhanced PDT. TPPa-Y NPs are prepared by encapsulating an ER-targeting pheophorbide-a (TPPa) and a hypoxia inducible factor 1α (HIF-1α) inhibitor (YC-1) with a hydrogen peroxide (H 2 O 2 )-responsive amphiphilic copolymer (PEG-PMPAP). After internalization into tumor cells, TPPa-Y NPs may rapidly dissociate and release both TPPa and YC-1. TPPa can target ER, which leads to an enhancement in its fluorescence signal and PDT efficacy. On the other hand, YC-1 may effectively inhibit the overexpressed HIF-1α and alleviate tumor hypoxia, which can further enhance the PDT efficacy of TPPa. Both in vitro and in vivo studies demonstrate that TPPa-Y NPs have a better anticancer effect than the nanoparticles without YC-1 (TPPa NPs). Therefore, this study provides a smart nanophotosensitizer, which is able to target ER and alleviate hypoxia for PDT efficacy enhancement. This work developed endoplasmic reticulum (ER)-targeting activatable nanophotosensitizers, which can selectively release ER-targeting photosensitizers and YC-1 within tumor cells for enhanced photodynamic therapy and hypoxia relief, respectively.